Meningkatkan kualitas hidup dan lingkungan masyarakat Desa Tadampalie Kecamatan Sabangbaru Kabupaten Wajo - Marsud Hamid (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Tadampalie Village is one of the villages in Sabbangparu Subdistrict which is in direct contact with the Walanae River which has the potential to produce fish. However, the problems faced are: 1) the lack of technology carried out by the community in processing and utilizing existing local potential, 2) limitations in managing fish catches, 3) the environment which is often flooded. Based on this basis, the KKN-PPM was agreed to be implemented in 2019. The main program is processing fish into fast food, smoked fish processing, and the application of appropriate technology in the utilization of environmental waste to produce organic fertilizer, so that with KKN-PPM quality is expected community life and environment will increase. The target groups are fishermen / farmers, housewives, young women, youth groups, PKK mothers, and small household industries that are domiciled in the KKN-PPM location. The methods used are training, mentoring, lecturing, practice and demonstration. The KKN-PPM activity also involved partner institutions, Wajo Regional Government and community leaders in Sabbangparu District. The number of students involved was 25 people with varied disciplines. Expected outputs are (1) the existence of processed fish products such as: nuget and shredded fish, (2) smoked fish, (3) fish smoke technology, and (4) technology available for making organic fertilizer and (5) fish smoke model simple. It is hoped that the quality of life and the environment of the community in Tadampalie Village can improve.